OC-026 Diagnostic Yields Of Sehcat Scanning And Glucose Hydrogen Breath Testing In Pelvic Radiation Disease. (9th June 2014) - Stacey, R; Turner, J; Green, J
Abstract : Introduction: Late Gastrointestinal side effects following radiotherapy are common but under reported by patients and poorly recognised by clinicians .1 Pelvic radiation disease (PRD) can present up to 30 years after radiotherapy treatment with a range of symptoms, including rectal bleeding, abdominal pain and diarrhoea. Many of these patients experience troublesome symptoms of diarrhoea secondary to Bile acid Malabsorption (BAM) and small intestinal bacterial overgrowth (SIBO). In our centre we have access to 23-seleno-25-homo-tauro-cholic acid (SeHCAT) nuclear medicine scanning and glucose hydrogen breath testing for the investigation of BAM and SIBO associated with PRD. The majority of data on patients with pelvic radiation disease has been published by one specialist centre (The Royal Marsden Hospital). We audited the diagnostic yields for investigation of small intestinal manifestations of PRD. Methods: We identified 77 patients referred to gastroenterology clinic at University Hospital Llandough, Cardiff with suspected pelvic radiation disease via a departmental database. All patients were investigated via the Royal Marsden algorithm and BSG guidance. We then identified all patients with diarrhoeal symptoms and audited the results of any SeHCAT and glucose hydrogen breath tests and their diagnostic yields. Results: 26 patients (36%) had diarrhoeal symptoms. Within this group, 24 patients underwent SeHCAT scanning, with 45% having positive results. 19 were referred for glucose hydrogen breath tests of which 53% had positive results. 17% had both positive SeHCAT and Glucose hydrogen breath tests. Not all patients received both tests due to various reasons (clinical decision, patient choice and non attendance). Conclusion: PRD is common but under investigated. BSG guidance on its management exists [1] and an algorithmic approach has been shown to be beneficial .2 Diarrhoea occurs frequently in PRD, and we have found that SeHCAT scanning and Glucose Hydrogen breath tests in these patients have a high diagnostic yield for BAM and SIBO respectively. SIBO and BAM can exist concurrently in this group, and our data supports a thorough and systematic algorithmic approach. Clinicians should have a low threshold for requesting these tests in patients with suspected PRD. References: 1 Andreyev HJN, Davidson SE, Gillespie C, Allum WH, Swarbrick E. British Society of Gastroenterology, et al . Practice guidance on the management of acute and chronic gastrointestinal problems arising as a result of treatment for cancer. Gut 2012:179–92 2 Andreyev HJN, Benton BE, Lalji A, Norton PC, Kabir M, Gage PH, et al . ArticlesAlgorithm-based management of patients with gastrointestinal symptoms in patients after pelvic radiation treatment (ORBIT): a randomised controlled trial. Lancet . Elsevier Ltd; 2013 Sep 20:1–9 Disclosure of Interest: None Declared.